Pengembangan Learning Materials untuk E-learning Mata Kuliah Metodologi Penelitian - Khaerudin; Mulyadi; Dinar Nur Syifa (Jurnal Pembelajaran Inovatif, 2021)
This development aims to produce a product in the form of learning materials for e-learning of Educational Research Methodology Course. The developed learning materials refer to the needs of the course and semester learning design that has been developed for the course, to facilitate learner in making more flexible and directed learning process. Development is carried out by Integrative Learning Design Framework Model with its three steps, they are, exploration information, enactment, and evaluation. The learning materials have gone through evaluation phase involving media experts, subject matter expert, instructional design expert, and users. Evaluation was carried out using open questionnaires to obtain descriptive data in the form of suggestions and input for product improvement. The follow up of the evaluation phase is some revisions of the product which include: color an text readability of the entire course site, changes in material display mode, formulation of learning objectives, concept map somponents, and learning object components.